Blue crush [videorecording (DVD)] - Weiss, Lizzy (Universal Studios Canada, 2002)
Ann-Marie, a big-wave surfer on the North Shore of Oahu, drives to make a comeback after nearly drowning in a surfing competition. Her life becomes more complicated by her romance with a handsome football player. Ann-Marie and her surfer buddies work as maids at a posh resort and share a beach shack with Anne-Marie's wayward young sister. Ann-Marie struggles between her need to prove herself and her desire to take the easy way out.